THE DISINTEREST OF RENTING RUSUNAWA IN BITUNG CITY - Ressa Rotinsulu; James D. D. Massie; Regina T. Saerang (Universitas Sam Ratulangi, 2023)
The rapid population growth in the city of Bitung has led to an increase in land prices. In response to this, the government of Bitung city created a residential facility, namely Rusunawa or also called Simple Rent Flats, Rusunawa is a place to live for low-income people. This study aims to find the reason why people in bitung city not interested in renting Rusunawa. This study use Descriptive Qualitative method, by collecting the data from the company, interview with the employee’s, and interview with people who choose to live in boarding house. The results of this study will be the reason why people choose to live in boarding house instead of Rusunawa and will be useful for the company in order to increase their occupants. Keyword: purchase intention